Dependence of flame height of internal fire whirl in a vertical shaft on fuel burning rate in pool fire. (5th July 2017) - Chow, W.K.; Dang, J.F.; Gao, Y.; Chow, C.L.
Highlights: An internal fire whirl (IFW) was generated by a pool fire in a vertical shaft. Flame height of the IFW was found to increase with the burning rate of pool fire. Semi-empirical formula for flame height was studied using experimental data. Dynamic and thermodynamic corrections were made on current flame height equation. Boiling of liquid fuel with combustion was observed during evolution of fire whirl. Abstract: An internal fire whirl (IFW) was generated by a pool fire in a vertical shaft with appropriate ventilation provision at the wall. The flame height of the IFW was found to increase with the burning rate of the pool fire. Semi-empirical formula for flame height in the IFW was studied analytically in this paper using reported experimental data from full-scale burning tests. Burgers vortex theory was applied for dynamic and thermodynamic corrections. From the experimental data, a rotating flame height coefficient was introduced to modify the empirical formula for the flame height in the IFW. Effects of thermal radiation and fuel vaporization were included to modify the calculation of the fuel burning rate.